Assessing the psychological, social and economic effects of caregiving on caregiver of mentally ill older patients accessing services at St John of God Hospital, Mzuzu - Chikopa, Fyness (Kamuzu University of Health Sciences, 2022)
Currently, in Malawi, there is scarcity of data on studies conducted on the psychological, social and economic effects of caregiving on caregivers of mentally challenged patients, who are also older persons above 60 years of age. Mentally challenged refers to all elderly suffering from any type of mental illness. A number of caregivers are affected psychologically, socially and economically due to their caregiving role, which affects quality of care, while little is done in managing these effects. Therefore, the study sought to identify psychological, social and economic challenges that affect the care-givers to inform the development of appropriate strategies. The study sought to describe how the psychosocial and economic effects of caregiving on caregivers of mentally ill older patients affects the quality of care of mentally ill older patients and documenting recommendations to address psychosocial and economic effects of caregiving on caregivers of mentally ill older patients. The study employed a cross-sectional design and qualitative research method. In-depth interviews were used to gather information from caregivers of older mentally ill patients and health workers who assist these elderly clients at St John of God Mental Health Clinic. A semi-structured interview guide was used by the researcher to acquire information from the respondents. A total of 22 people participated in the study; 14 caregivers and 8 health workers. All the participants were above 18 years of age. The caregivers were 14; 8 females and 6 males, respectively. The health workers were 8; 3 clinicians and 5 nurses. Data collection was done from 22nd October to 20th November, 2020. Data was analysed using thematic analysis. Ethical clearance to conduct the study was obtained from the College of Medicine Research Ethical Committee (COMREC). Female caregivers were more depressed than male caregivers. The caregivers experienced stigma and discrimination and were isolated in their communities because they cared for the older mentally challenged patients. Caregivers were also faced with financial problems, which affected the quality of health care provided to the patient by the caregivers since the caregivers were affected. Recommendations were made to ensure caregivers provided quality care, including provision of support to the caregivers by the relatives; the health workers to provide mental health education to prevent stigma and discrimination in the community and the government to ensure that mental health service is available in all their health facilities. Caregivers face social, psychological and economic problems during their provision of care to mentally ill older patients. There is need to provide comprehensive management of caregivers in order to alleviate these problems for the patient to receive quality care.